Refleksi Coaching Pengawas Sekolah Dasar - Astari, Tri (EDUPEDIA Publisher, 2022)
This activity aims to reflect on coaching school supervisors to discover the coaching process that has been carried out and to deepen the competence of coaching school supervisors. The method used in this coaching reflection consists of preparation, implementation, and evaluation of activities. The results of the coaching reflection showed that school supervisors had yet to carry out coaching activities as scheduled once a month. While the findings in the school supervisor's review on coaching are that all this time, school supervisors understood coaching differently from its true meaning. Even though there has been a meeting between the school supervisor and the principal, this is not coaching but facilitation or mentoring, which is dominated by providing suggestions or solutions and is carried out with the school's teachers. Through deepening the meaning and competency of coaching again, it can be concluded that participants understand coaching better than before, and they have committed to coaching school principals in the Program Sekolah Penggerak.